Soil nutrient status and forage yield at varying distances from trees in four dehesas in Extremadura, Spain (Silvopastoralism and Sustainable Land Management: Proceedings of an International Congress on Silvopastoralism and Sustainable Management Held in Lugo Spain, in April 2004, 2006)
The aim of this study was to understand the effect of holm-oak (Quercus ilex) on the soilnutrient concentration and its consequence on the yield of understory forage (Avena sativa) in four dehesas of CW-Spain. The soils of the dehesas varied in soil fertility (chromic Luvisols and Achrisols, and eutric Leptosols). Forage dry-matter yields were determined from 1-m2 sample plots at distances ranging from 2 to 20 m from the tree (9 trees per farm and year). Soil samples (0-30 cm depth) were also collected from the same sampling locations, and were analysed for pH, Electrical Conductivity, organic C, CEC, total-N, available N and base cations. Soil analysis results showed that the most of the values increased in the vicinity of the tree: organic C, total-N, CEC and exchangeable Ca2+ and K+. Differences in forage yield were mainly explained by fertilization dosage, light availability (estimated from Montero and Moreno, 2004) and soil CEC. In more fertile soils, forage production was negatively effected by the presence of the trees, as a consequence of light reduction (Competence), while in more oligotrophic soils, forage production was positively affetced by trees (Facilitation).